Non-constant hazard function and inflation dynamics - Fang Yao (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
This paper explores implications of nominal rigidity characterized by a non-constant hazard function for aggregate dynamics. I derive the NKPC under an arbitrary hazard function and parameterize it with the Weibull duration model. The resulting Phillips curve involves lagged inflation and lagged expectations. It nests the Calvo NKPC as a limiting case in the sense that the effects of both terms are canceled out under the constant-hazard assumption. Furthermore, I find lagged inflation always has negative coefficients, thereby making it impossible to interpret inflation persistence as intrinsic. The numerical evaluation shows that the increasing hazard function leads to hump-shaped impulse responses of inflation to monetary shocks, and output leads inflation.
Keywords: E12; E31; 330; Hazard function; Weibull distribution; New Keynesian Phillips Curve; New-Keynesian Phillips Curve; Statistische Bestandsanalyse; Preisrigidität; Theorie; Inflation; Lag-Modell; Theorie